Une methode de pseudo-concentration pour Ia simulation 3D volumique du remplissage de monies d ’injection - Abbes, Boussad; Ayad, Rezak; Rigolot, Alain (European Journal of Computational Mechanics, 1999)
A full 3D filling algorithm for injection moulding of molten polymers is presented. The non-Newtonian fluid flows governing equations are solved using a mixed velocitypressure finite element formulation with a mini-element. To track the polymer front, a transport equation of a pseudo-concentration function is solved using a control volume technique. The ability of the proposed algorithm to simulate the filling of three-dimensional moulds is demonstated through complicated flows and geometries examples.